Determinants of Patient Safety Competence Among Diploma-Level Nursing Students in Jakarta - Linda, Silvana Evi; Lindayani, Linlin (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Ensuring patient safety is a core component of healthcare quality; however, the persistence of medical errors highlights an ongoing global challenge. In Indonesia, Diploma III nursing programs are instrumental in preparing novice nurses, yet variability in curriculum design and clinical experience may affect their ability to uphold safety standards. Objective: This study aimed to identify factors associated with patient safety competence among Diploma III nursing students in Jakarta, Indonesia. Methods: A cross-sectional design was applied, involving 200 students from accredited Diploma III nursing institutions in Jakarta. Participants were recruited through multistage cluster sampling. Data collection utilized a structured survey comprising the Health Professional Education in Patient Safety Survey (H-PEPSS), the Quality of Clinical Learning Environment (QCLE) Scale, and the General Self-Efficacy Scale (GSES). Multiple linear regression analysis identified key predictors of safety competence. Results: Patient safety competence demonstrated significant positive associations with self-efficacy (r = 0.52, p < 0.001), quality of training (r = 0.41, p < 0.001), and institutional culture (r = 0.34, p < 0.001). Regression results revealed that self-efficacy (β = 0.42, p < 0.001) and training quality (β = 0.26, p = 0.002) significantly predicted competence, jointly explaining 37.2% of the variance. Institutional culture, however, was not a significant predictor (β = 0.09, p = 0.118). Conclusion: Self-efficacy and clinical training quality are key contributors to patient safety competence in Jakarta’s Diploma III nursing students. Educational strategies targeting these domains may enhance safety outcomes. Future research should explore the long-term influence of institutional culture.